Experiment in Progressive Patient Care. Issue 5621 (28th September 1968) - Hartley, Ronald; O'Flynn, W. R.; Rake, Mark; Wooster, Mary
Abstract : A successful experiment is described in providing total progressive patient care in a small hospital. This was based on dividing ward services into nursing and "hotel" services, the latter being provided by a housekeeping team. Patients were divided into three categories according to the amount of nursing care needed, and two wards were converted, one into an intensive care unit, the other into a homeward bound unit, with high and low nurse/patient ratios respectively.